Phosphorus recovery by struvite precipitation: a review of the impact of calcium on struvite quality - Isaac Enyemadze (IWA Publishing, 2021)
Precipitation of phosphorus (P) as a struvite product from wastewater and local magnesium (Mg) sources is considered as a high economical prudent venture, as it has shown to bring down the cost of producing the product. However, there is a significant concentration of calcium (Ca) in these Mg and most wastewater sources. The presence of Ca in wastewater and Mg sources during struvite precipitation has been shown to negatively affect the quality of the struvite produced. The low struvite quality greatly impedes its use as a fertiliser given the economic value of the product as an alternative P fertiliser. This review paper provides an understanding of how the presence of Ca affects the purity, crystal size, and morphology of the struvite. Different methods that have been used to mitigate the effect of Ca on struvite quality have been reviewed. The factors that affect the recovery of P and the percentage recoveries of P by different Mg sources have also been reviewed. This paper serves as a basis for further research where the possibility of removing Ca from wastewater and Mg sources is explored. When Ca is removed before struvite precipitation is carried out, the quality of the product will be greatly improved. HIGHLIGHTS Trend analysis of impact of Ca on struvite quality has been done.; All methods for the mitigation of the negative impact of Ca have been reviewed.; Nutrient removal efficiencies of Mg sources have been compared.; Molar ratios that affect struvite quality have been identified.; Research gap for improving struvite quality has been identified.;